One-Pot Conversion of 1-Bromo-β-carboline and 1-Bromocarbazole into Pentacyclic Compounds by Suzuki Cross-Coupling Followed by Spontaneous Cyclization - Gehring, André P.; Tremmel, Tim; Bracher, Franz (Synthesis, 2014)
This work describes a straightforward one-pot conversion of 1-bromo-β-carboline and 1-bromocarbazole into pentacyclic compounds. Suzuki cross-coupling with various 2-methoxycarbonylphenylboronic acids was followed by spontaneous lactamization to give the target products. Coupling of 1-bromo-β-carboline with 2-formylphenylboronic acid also gave the oxo product through oxidative cyclization, whereas in the carbazole series, the intermediate hemiaminals undergo a disproportionation reaction to give both the oxo and the methylene product.
Keywords: cross-coupling; canthines; β-carbolines; carbazoles; oxidative cyclization